ISLAMIC FINANCE, GREEN INNOVATION AND FINTECH: A TRIPLE BOOST FOR MSME FINANCIAL GROWTH - Widyastuti, Emy; Futuha, Darul; Purwaningrum, Devvy Ayu; Yudhiana, Fetria Eka; Nabhan, Faqih; Ariyani, Diyah; Nabila, Rifda (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Indonesia has a large number of MSMEs but does not have good financial performance, thus hindering its development. This research focuses on the analysis of the determinants of MSME financial performance through Islamic financial literacy and inclusion, green innovation with financial technology as a moderator. The research was conducted in Demak Regency through a quantitative approach. The population is aimed at Food and Beverage MSMEs in Demak district. The data source was obtained through primary data with questionnaire instruments. To obtain a representative sample, samples will be taken using purposive sampling techniques so that 100 respondents are obtained. The findings through PLS's Structural Equation Modelling (SEM) explained that Islamic financial literacy and green innovation have a significant contribution to improving positive financial performance in MSMEs. Islamic financial inclusion has a positive influence on the performance of MSMEs but is not significant. Fintech cannot strengthen Islamic financial literacy and inclusion in financial performance. The use of financial technology can strengthen the influence of green innovation on the financial performance of MSMEs. These findings contribute to improving the financial performance of MSMEs involving sharia finance factors and the ability to innovate.